Epileptic-like symptoms and stress conditions in adolescents - Bob, Petr; Selesova, Petra; Kukla, Lubomir (Perceptual and motor skills, 2012)
According to recent clinical data, epileptiform changes in temporolimbic structures may be related to psychopathological symptoms known to be related to stress. These data are also consistent with findings that temporal lobe epileptiform activity may provoke various somatic, sensory, behavioral, and memory disturbances similar to temporolimbic seizures and may lead to complex partial seizure-like symptoms which may also occur in nonepileptic conditions. Together, these findings suggest a hypothesis concerning the extent to which psychopathological changes usually related to stress may be associated with complex partial seizure-like symptoms or whether these symptoms might more likely be explained by various somatic factors. To test the hypothesis in a sample particularly vulnerable to stress, these relations between stress-related psychopathology and complex partial seizure-like symptoms were examined in a sample of 340 adolescents. Complex partial seizure-like symptoms were significantly associated with stress-related psychopathology: even mild stress may cause symptoms similar to cognitive and affective disturbances observed in patients with complex partial seizures.
Keywords: průzkumy a dotazníky; Female; Seizures; úzkost; mladý dospělý; ženské pohlaví; psychický stres; Surveys and Questionnaires; Adolescent; lidé; Anxiety; Male; depresivní poruchy; Stress, Psychological; psychiatrické posuzovací škály; Young Adult; Depressive Disorder; deprese; mužské pohlaví; Depression; mladiství; Psychiatric Status Rating Scales; záchvaty; Humans